Creativity, aesthetics and ethics of food waste in social media campaigns. (10th September 2018) - Närvänen, Elina; Mesiranta, Nina; Sutinen, Ulla-Maija; Mattila, Malla
Abstract: A majority of food waste in developed countries is caused by households. Previous studies have focussed on explicating reasons and contexts for food waste, whereas consumer-oriented solutions still need further study. This study investigated how sociocultural meanings of household food waste reduction were negotiated in social media campaigns. It adopted an interpretive approach through a qualitative case study and utilised interviews and online materials as data. The study identified three sociocultural themes, creativity, aesthetics and ethics of food waste, interlinked through connections with food, waste and social media. The analysis elaborated how these three broader positive sociocultural meanings were used in the studied social media campaigns to (re)negotiate the food waste phenomenon. The paper proposes that highlighting positive meanings of food waste which resonate with consumers and facilitating consumer-to-consumer communications are potential ways to address sustainability issues. Highlights: Social media campaigns can create and maintain positive sociocultural meanings of food waste. Identified positive meanings: creativity in reducing food waste, aesthetics of food waste, and ethics of food waste. The sociocultural context and everyday realities of consumers are important in designing consumer-directed campaigns. Empowering consumers to participate in the discussion on food waste enables cooperative and shared ways of communication.